Numerical Simulation Methods of Electromagnetic Field in Higher Education: Didactic Application with Graphical Interface for FDTD Method - Osaci, Mihaela (International journal of modern education and computer science, 2018)
In general, the act of teaching in universities of the numerical methods of electromagnetic field simulation is a rather difficult action. In order to facilitate this act, it is necessary to use modern didactic means that complement the classical ones, so that the students understand in an interactive manner the method, the algorithm and its implementation into a programming language. This paper proposes a didactic method able to facilitate the understanding of numerical methods in electromagnetism. It's about of a didactic application with graphical interface, programmed using the Guide Matlab to simulate the electromagnetic waves propagation through various environments and applying the finite-difference time-domain method (FDTD).